Analisis Penerapan Fuzzy Inference System (FIS) Dengan Metode Mamdani Pada Sistem Prediksi Mahasiswa Non-Aktif (Studi Kasus: STMIK Budi Darma) - Nurul Nining Apriani (JURIKOM (Jurnal Riset Komputer), 2019)
STMIK BUDI DARMA is a college in the developing city. The number of college students makes it difficult to handle student activity data processing. The emergence of problems - often implementation problems arise, one of which is the number of non-active students. The high level of success of students and the low level of failure can reflect the quality of higher education. Research has been done statistically for this. At the writing of this thesis a system was developed that would predict non-active students using Object Oriented analysis systems and Fuzzy Inference Systems (Fis) using input variables. Prediction is done by entering parameters so that conclusions can be drawn on how much the level of non-active students is